PTSD and Suicides Among Veterans—Recent Findings. (12th September 2017) - Koven, Steven G.
Abstract : The mental health of military personnel returning from war is an issue of profound social, ethical, and economic consequence. This article reviews recent literature from academic journals, government agencies, and think tanks related to veterans' PTSD and suicides. The review finds that most studies identify clear linkages between PTSD, suicide, and military service. The conceptual frameworks of utilitarianism and deontology are presented as two viable ethical frameworks for assessing veteran mental health policies. Practical considerations of national security as well as categorical principles are presented as useful lenses to assess the ethicality of policy.